Refractive errors and associated factors among patients visiting BoruMeda Hospital's secondary eye Unit in Dessie Town, South Wollo Zone, Ethiopia. - Besufikad, Bersabeh; Hailemichael, Wasihun; Tilahun, Lehulu; Yimam, Wondwossen; Anteneh, Samuel (BMC Ophthalmology, 2022)
Background: In Ethiopia, refractive error is the second leading cause of vision impairment and the third main cause of blindness. Because refraction services are scarce and difficult to obtain, many people with refractive error live with impaired vision or blindness for the rest of their lives.Objective: The primary goal of this study was to determine the prevalence of refractive errors and associated factors among patients who visited Boru Meda Hospital.Methods: A retrospective cross-sectional study was conducted from April to June 2018, all patients who visited Boru Meda Hospital's secondary eye unit were deemed our source population; the sample frame was the secondary eye unit outpatient departments register. To select samples, simple random sampling was used. Data was entered by using Epi-data version 3 and analysed with Statistical Package for Social Science 20. Tables and graphs were used to display descriptive statistics, and logistic regression was used to examine the relationship between the dependent and independent variables. At p < 0.05, statistical significance was inferred.Results: Refractive error was detected in 42 (18.3%) of study participants. The average age was 46.69 ± 20.77. There were 136 men and 93 women in this group (59.4 and 40.6%, respectively). Myopia was the most frequent refractive defect, accounting for 52.4% of all cases.Conclusion& Recommendation: Refractive error is a widespread problem in our study area that affects people of all age groups. We recommend patients to have screening on regular basis so that refractive anomalies can be detected early.